Behaviour of expansive clay when it absorbs water - Tan, Soon Hong. (2010)
Geotechnical engineers have been having problem with soils due to the expansive nature of clay. This is mainly due to the minerals that exist in clay. The affinity to water of montmorillonite in clay has caused different swelling pressures due to the variations in the moisture content of the soils. Expansive soils have the potential for shrinking and swelling under moisture variations as stated by Nelson.